Downregulation of Notch Signaling‐Stimulated Genes in Neurovascular Unit Alterations Induced by Chronic Cerebral Hypoperfusion - Dewen Ru; Zengyu Zhang; Meng Liu; Xuhui Fan; Yuqi Wang; Yufeng Yan; Ersong Wang (Immunity, Inflammation and Disease)
ABSTRACT Background Chronic cerebral hypoperfusion (CCH) is a key contributor to vascular cognitive impairment (VCI) and is typically associated with blood–brain barrier (BBB) damage. This study investigates the pathological mechanisms underlying CCH‐induced neurovascular unit (NVU) alterations. Methods A mouse model of CCH was established using the bilateral common carotid artery stenosis (BCAS) procedure. Decreased cerebral blood flow (CBF) and impaired BBB integrity were assessed. Brain microvessel (BMV)‐specific transcriptome profiles were analyzed using RNA‐seq, supplemented with published single‐cell RNA‐seq data. Results RNA‐seq revealed neuroinflammation‐related gene activation and significant downregulation of Notch signaling pathway genes in BMVs post‐BCAS. Upregulated differentially expressed genes (DEGs) were enriched in microglia/macrophages, while downregulated DEGs were prominent in endothelial cells and pericytes. Enhanced activation of vascular‐associated microglia (VAM) was linked to neurovascular alterations. Conclusion CCH induces significant NVU changes, marked by microglia‐associated neuroinflammation and Notch signaling downregulation. These insights highlight potential therapeutic targets for treating neuroinflammatory and vascular‐related neurodegenerative diseases.